Carbon Stock Mapping in the Area of West Oesapa Mangrove Forest Ecotourism using Sentinel-2a Imaginery - Maria Edelin; Yofris Puay; Aah Ahmad Almulqu; Dimaz Danang Al-Reza; Khozanah Syifa; Dwi Wahyuni; Anasufi Banawi (INSTITUT AGAMA ISLAM NEGERI AMBON, 2026)
This research is motivated by the prevailing issue of global warming, characterized by the increase in the average temperature of the Earth's atmosphere, leading to climate change. In climate change mitigation efforts, mangrove forests play an important role by effectively storing and absorbing substantial quantities of carbon, subsequently sequestering it in the form of biomass. This study aims to estimate the potential of carbon stocks stored in the area of West Oesapa Mangrove Forest Ecotourism, estimate CO2 uptake, and determine the correlation between NDVI vegetation index and carbon stock/storage. This research was conducted for two months, started from November to December 2023 at the West Oesapa Mangrove Forest Ecotourism. The research stages consisted of pre-image processing, image processing, field survey, and data analysis. The species allometric formula was utilized to calculate mangrove biomass, which was then converted into carbon stock values in mangrove forests. Sentinel-2A images were transformed with Normalized Difference Vegetation Index (NDVI), then regression analysis was conducted between NDVI and carbon stock values to obtain a carbon stock estimation model using satellite imagery. There are five mangrove species found, namely Sonneratia alba, Avicenia alba, Rhizophora stylosa, Rhizhopora mucronate, and Burguiera. The results indicated that the estimated carbon stock stored in the West Oesapa Mangrove Forest Ecotourism was 3,852.36 tons/ha. Meanwhile, the estimated CO2 uptake in the West Oesapa Mangrove Forest Ecotourism is 14,125.32 tons/ha. The results of the person correlation analysis with a correlation coefficient of 0.608 means that the NDVI variable and carbon stocks are correlated or have a relationship. Keywords: Biomass, Mangrove Carbon, Allometric Calculation, Sentinel 2A Imagery, NDVI